Artrografía mediante resonancia magnética con solución fisiológica en el diagnóstico de la perforación del disco de la articulación temporomandibular. Reporte de caso - Gómez, Marcos (2024)
Partial or total perforation of the articular disc is mainly observed in the final stage of temporomandibular disorder. Magnetic resonance imaging (MRI) is considered the gold standard for the diagnosis of joint pathologies; MRI arthrography consists of the infiltration of a contrast medium into a joint, being Gadolinium chelates the most employed medium, however, possible harmful effects have been associated with its use. The aim of this work was to evaluate a case of perforation of the articular disc of the temporomandibular joint by MRI arthrography using physiological solution (NaCl 0.9%) as contrast medium. MR images were obtained with a STIR (Short Tau Inversion Recovery) weighted pulse sequence in the sagittal and coronal planes at maximum mouth opening, after the injection of the physiological solution in the superior articular space. The communication of both articular spaces was identified, observing a greater filling in the inferior articular space, as well as the latero-medial displacement of the disc segments. Arthrography with physiological solution allowed the precise diagnosis of the perforation, which made it possible to guide the treatment plan, reducing diagnostic and surgical times, also considering the reduction of complications and adverse effects related to other contrast media, added to the benefit of the reduction of the cost of the exam.